Needs Analysis of a 360° Virtual Tour as Campus Information Medium at STTNF Using PIECES - Annisa Nurul Nabilah; Jemiro Kasih (P3M Politeknik Negeri Bengkalis, 2026)
This study aims to analyze the system requirements for developing a 360° Virtual Tour as a campus information medium for Nurul Fikri Integrated Technology College (STTNF) using the PIECES model, comprising Performance, Information, Economy, Control, Efficiency, and Service dimensions. A descriptive qualitative approach was employed, with data collected through observation, semi-structured interviews, and documentation involving 15 informants consisting of prospective students, active students, and New Student Admission Team representatives. Data were analyzed through transcription, coding, categorization, technique triangulation, mapping into the PIECES dimensions, and requirements formulation. The credibility of the findings was strengthened through member checking. The findings reveal that existing campus information media at STTNF remain static and non-interactive, limiting users from obtaining a comprehensive overview of the campus environment. Based on the PIECES analysis, 23 functional requirements and 22 non-functional requirements were formulated, with information completeness, navigation support, and system performance emerging as the primary user priorities. An initial use case diagram was developed to translate the validated requirements into a preliminary system model. This study contributes a validated and user-centered requirements specification for campus-based 360° Virtual Tour development using the PIECES model, distinguishing itself from prior studies that focused predominantly on implementation and usability evaluation by emphasizing requirements elicitation prior to system development in higher education institutions.